Application of narrow‐band imaging in upper urinary urothelial carcinoma: A preliminary report. Issue 2 (May 2014) - Chan, Eddie Shu‐Yin; Ng, Chi‐Fai; Chan, Chi‐Kwok; Hou, See‐Ming; Yip, Sidney Kam‐Hung
<x xml:space="preserve">Abstract</x> Aim In the present study, the performance of narrow‐band imaging (NBI) ureteroscopy in the detection of upper urinary tract transitional cell carcinoma (TCC) was evaluated. Patients and Methods Ureteroscopies were carried out using both white‐light imaging (WLI) and NBI in patients with known upper urinary tract TCC before definitive treatment. Biopsies were performed when abnormal lesions were detected. The number of lesions found in WLI and NBI ureteroscopies, and histological findings, were compared with final pathological reports on nephroureterectomy or segmental resection specimens. Results Seven patients with eight upper urinary tract TCC were examined using WLI/NBI ureteroscopy between 2010 and 2011. Complete examinations failed in two patients, due to ureteric strictures. After ureteroscopy, five nephroureterectomies and two segmental resections were performed in this series. Endoscopic laser resection of the ureteric tumour was performed successfully under WLI/NBI in one patient. NBI ureteroscopy detected two more lesions than WLI, both of which were found to be benign in the final histological analysis. No other lesions in the nephroureterectomy specimens escaped detection during the ureteroscopic examination. Conclusion NBI ureteroscopy is technically feasible for upper urinary tract examination. It did not improve TCC detection rate compared with conventional WLI. Further studies might be necessary for the evaluation of its use and efficacy.